2015
DOI: 10.22409/revistaleph.v0i23.25056
|View full text |Cite
|
Sign up to set email alerts
|

Formação De Professores Para O Atendimento Educacional Especializado: Políticas E Práticas Instituintes De Inclusão

Abstract: O artigo apresenta resultados parciais de investigações empreendidas no Observatório da Educação Especial do Estado do Rio de Janeiro, inserido no Observatório Nacional da Educação Especial. Desde 2011, avaliamos os limites e possibilidades das Salas de Recursos Multifuncionais implementadas nos municípios do Rio de Janeiro, Niterói, Petrópolis e Nova Iguaçu, com a parceria de quatro universidades públicas. Apresentamos um mapeamento sobre o eixo formação de professores para inclusão escolar e a proposta do I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this sense, it is observed that several international studies (Booth, 2011;Cansino, 2010;Moliner, Sales, Ferrández, & Traver, 2011;Salceda Mesa & Ibanez Garcia, 2015) as well as Brazilians (Lago, 2014;Fernandes, 2014;Santos, Santiago, & Melo, 2015;Araujo, 2013;Silva, 2012) already use the "Index for Inclusion" in continuing education programs. The results of these studies point out that the document can be a way of strengthening reflections in everyday school life on inclusive cultures, practices and policies.…”
Section: Sustainabilitymentioning
confidence: 99%
“…In this sense, it is observed that several international studies (Booth, 2011;Cansino, 2010;Moliner, Sales, Ferrández, & Traver, 2011;Salceda Mesa & Ibanez Garcia, 2015) as well as Brazilians (Lago, 2014;Fernandes, 2014;Santos, Santiago, & Melo, 2015;Araujo, 2013;Silva, 2012) already use the "Index for Inclusion" in continuing education programs. The results of these studies point out that the document can be a way of strengthening reflections in everyday school life on inclusive cultures, practices and policies.…”
Section: Sustainabilitymentioning
confidence: 99%